The Reflected Mythological Patterns on Researchers' Journey through Literacy Narratives (Universitas Islam Negeri Sunan Ampel Surabaya, 2019)
This paper aims to provide a heroism mythological reflection on the journey of researchers. This study uses the qualitative case study to obtain the comprehension of researchers' metaphor journeys through Monomyth on their research experiences. The documentary analysis is used in this qualitative study with the reflexive narrative because the reflection on experience can help the reader to gain insight into the researcher and their approach during the journey. 15 researchers' literacy narratives chosen in this study which consists of 8 published literacy narratives and 7 literacy narratives task from participants. Research itself often considered as a journey that extends the existing knowledge and also develops new knowledge of the researcher while wandering in the wilderness of knowledge. Along the way, the researchers with their literacy narratives in this study unconsciously have a similar mythical pattern story as like as the mythical heroes which Campbell (1949) term it as Monomyth pattern. The result presented in this paper may facilitate the literate improvements in which to motivate, to help the novice researcher to understand their own hero's journey and to educate them about the stages that they will experience such as their new transition of conducting their new research.